2014
DOI: 10.1080/08934215.2014.927518
|View full text |Cite
|
Sign up to set email alerts
|

When an Instructor Swears in Class: Functions and Targets of Instructor Swearing from College Students’ Retrospective Accounts

Abstract: Via a communication competence lens, students' accounts of instructor swearing were inductively analyzed to understand students' perceptions of the swear word's function and target. Coding revealed seven functions of teacher swearing: emphasize=elaborate, accommodate students, be humorous, show frustration, gain attention, instructor personality=disposition, and accidental. Six targets of teacher swearing were also found: swearing directed toward course content, noncourse content, the self (instructor), studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Responses to swearing have also been studied in the education setting. Generous et al (2015) examined students' retrospective accounts of instructor swearing in the classroom.…”
Section: Swearing and Perceptions Of The Speakermentioning
confidence: 99%
“…Responses to swearing have also been studied in the education setting. Generous et al (2015) examined students' retrospective accounts of instructor swearing in the classroom.…”
Section: Swearing and Perceptions Of The Speakermentioning
confidence: 99%
“…Students may view instructors swearing to appear approachable as negatively violating their expectations of professional instructor behavior, including the social distance professors are expected to maintain with students. Generous, Frei, and Houser, (2015) have suggested students might view instructor swearing to accommodate students as belittling. They concluded that “teachers who swear for relational purposes should be careful” (Generous, Frei, & Houser, 2015, p. 137).…”
Section: Hypothesesmentioning
confidence: 99%
“…Generous, Frei, and Houser, (2015) have suggested students might view instructor swearing to accommodate students as belittling. They concluded that “teachers who swear for relational purposes should be careful” (Generous, Frei, & Houser, 2015, p. 137).…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations